Meningkatkan Keterampilan Vokasional Membuat Hiasan Dinding dari Stik Es Melalui Model Explicit Instruction pada Anak Tunagrahita Ringan - Aryati, Devia; Armaini, Armaini (Kognitif: Jurnal Pendidikan dan Inovasi Pembelajaran, 2024)
This research is motivated by the problems found in class VIII SLB WacanaAsih, in one practice room there are five students with mild mental retardation and a duo of students who are not yet skilled in making wall decoration skills from ice sticks. Previously the children had learned skills from ice sticks such as making pencil boxes or markers but they were not successful in the process, therefore this research was conducted using ice sticks through an explicit instruction model, in this research it will be carried out in two cycles, each cycle consisting of: planning, the implementation of action, observation and reflection. The data collection techniques used were observation, documentation, and action tests. Based on the results obtained by students using two cycles, namely the value of Ga in the first cycle of action, namely 88.7%, and in the second cycle obtained a value of 91.9%, while Ge students obtained a value in the first cycle of 64.5%, and in cycle II obtained a value of 82.3%, Gi students in the action cycle I was 88.7%, and in cycle II obtained a value of 91.9%, Fa students in the action cycle I was 88.7%, and in cycle II II obtained a value of 91.9%, and Pu students in the first cycle of action was 74.2%, and in cycle II obtained a value of 85.5%. Based on the data above, the conclusion of the skill of making wall decorations from ice sticks has increased significant through an explicit instruction model.